Active angular tuning and switching of Brewster quasi bound states in the continuum in magneto-optic metasurfaces - Abujetas Diego R. (De Gruyter, 2021)
Bound states in the continuum (BICs) emerge throughout physics as leaky/resonant modes that remain, however, highly localized. They have attracted much attention in photonics, and especially in metasurfaces. One of their most outstanding features is their divergent Q-factors, indeed arbitrarily large upon approaching the BIC condition (quasi-BICs). Here, we investigate how to tune quasi-BICs in magneto-optic (MO) all-dielectric metasurfaces. The impact of the applied magnetic field in the BIC parameter space is revealed for a metasurface consisting of lossless semiconductor spheres with MO response. Through our coupled electric/magnetic dipole formulation, the MO activity is found to manifest itself through the interference of the out-of-plane electric/magnetic dipole resonances with the (MO-induced) in-plane magnetic/electric dipole, leading to a rich, magnetically tuned quasi-BIC phenomenology, resembling the behavior of Brewster quasi-BICs for tilted vertical-dipole resonant metasurfaces. Such resemblance underlies our proposed design for a fast MO switch of a Brewster quasi-BIC by simply reversing the driving magnetic field. This MO-active BIC behavior is further confirmed in the optical regime for a realistic Bi:YIG nanodisk metasurface through numerical calculations. Our results present various mechanisms to magneto-optically manipulate BICs and quasi-BICs, which could be exploited throughout the electromagnetic spectrum with applications in lasing, filtering, and sensing.